PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN CITY CAR KIAPICANTO PADA PT. KARS INTI AMANAH (KALLA KIA) PALU - Sudirman, Sudirman (Katalogis, 2015)
The aims of this study are: 1) to seek and analyze simultaneous influence of product, price, promotion, and place on consumers’ purchasing decisions; 2) to seek and analyze the influence of product on consumers’ purchasing decisions; 3) to seek and analyze the influence of price on consumers’ purchasing decisions; 4) to seek and analyze the influence of promotion on consumers’ purchasing decisions; 5) to seek and analyze the influence of place on consumers’ purchasing decisions. Sample of this study consists of 61 people who selected through purposive sampling technique. The hypotheses are tested with multiple linear regressions. The result show that: 1) product, price promotion, and place simultaneously have significant influence of consumers’ purchasing decisions; 2) product influences consumers’ purchasing decisions positively but insignificantly; 3) price positively and significantly influences consumers’ purchasing decisions; 4) promotion positively and significantly influences consumers’ purchasing decisions; 5) place negatively and significantly influences consumers’ purchasing decisions.